2021
DOI: 10.1002/wmh3.474
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost alternatives for the management of Guillain‐Barré syndrome in low‐ and middle‐income countries

Abstract: Guillain‐Barré syndrome (GBS) is the most common cause of acute flaccid paralysis. It can cause rapidly progressing ascending paralysis leading to respiratory failure. There is no definite treatment for GBS, but early administration of intravenous immunoglobulin or therapeutic plasma exchange accelerates motor recovery and decreases time on the ventilator support and are considered the standard of care in GBS. However, these treatments are often unaffordable for many patients in low‐ and middle‐income countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“… 3 , 24 Similarly, a Chinese study showed that incidence of the disease peaked in children aged 1–4 years. 7 In this study, the mean age of the participants (7.25±3.91 years) is in line with findings of other studies; 7 , 13 and 35.3% of them were under 5 years of age which is consistent with a report from China. 8 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“… 3 , 24 Similarly, a Chinese study showed that incidence of the disease peaked in children aged 1–4 years. 7 In this study, the mean age of the participants (7.25±3.91 years) is in line with findings of other studies; 7 , 13 and 35.3% of them were under 5 years of age which is consistent with a report from China. 8 …”
Section: Discussionsupporting
confidence: 92%
“…3,24 Similarly, a Chinese study showed that incidence of the disease peaked in children aged 1-4 years. 7 In this study, the mean age of the participants (7.25±3.91 years) is in line with findings of other studies; 7,13 and 35.3% of them were under 5 years of age which is consistent with a report from China. 8 Some studies showed clustering in the incidence of GBS during certain seasons of the year: an observation that can be explained by the seasonality of certain triggers of GBS like gastroenteritis and influenza.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, the utilization of small-volume TPE methods, whether through centrifugation or membrane separation, offers further cost savings and has been widely implemented in LMICs. 70 Another alternative is small-volume plasma exchange (SVPE) by sedimentation, which involves repeated removal of small volumes of plasma over several days using sedimentation of the patient's whole blood, eliminating the need for a centrifugation machine. The sedimented blood cells are then re-transfused to the patient along with normal saline and fresh frozen plasma as replacement fluid.…”
Section: Inpatient Management Of Guillain-barré Syndromementioning
confidence: 99%